At Pyramid Lake - Mergen, Bernard 1937- (Univ. of Nevada Press, 2014)
"Pyramid Lake is one of the largest lakes in the Great Basin, the terminus of the Truckee River flowing from Lake Tahoe into northern Nevada. This desert oasis, with a surface area of nearly two hundred square miles, is a unique geological feature and was home to the Paiute for thousands of years before the arrival of explorer John C. Fremont in 1844. For the Paiute, it was a spiritual center that provided life-sustaining resources, such as the cui-ui, a fish unique to the lake and now endangered. For the ranchers and farmers who settled on tribal lands, the waters that flowed into it were necessary to raise cattle and crops. Mergen tells how these competing interests have interacted with the lake and with each other, from the Paiute War of 1860 to the present. The lake's very existence was threatened by dams and water diversion; it was saved by tribal claims, favorable court decisions, improved water laws, and the rise of environmentalism. At Pyramid Lake is about more than Indians and water wars, however. It is the story of railroads on the reservation and the role of federal, state, and private groups interested in sportfishing. It is about scientists, artists, and tourists who were captivated by the lake's beauty. Finally, it is also a story of the lake as a place of spiritual renewal and celebration. Mergen grew up near its shores in the 1940s and returned frequently through the years. In this cultural history, he combines his personal remembrances with other source material, including novels, poetry, newspaper and magazine journalism, unpublished manuscripts, and private conversations, to paint a fascinating portrait of one of Nevada's natural wonders"..